The Use of Age Assessment in the Context of Child Migration: Imprecise, Inaccurate, Inconclusive and Endangers Children's Rights - Ranit Mishori (MDPI AG, 2019)
Anecdotal reports suggest migrant children at the US border have had to undergo age assessment procedures to prove to immigration officials they qualify for special protections afforded to those under age 18. There are a variety of methods to assess the chronological ages of minors, including imaging studies such as X-rays of the wrist, teeth, or collarbone. However, these procedures have come under great scrutiny for being arbitrary and inaccurate, with a significant margin of error, because they are generally based on reference materials that do not take into account ethnicity, nutritional status, disease, and developmental history, considerations which are especially relevant for individuals coming from conflict and/or resource-constrained environments. Using these procedures for migration purposes represent an unethical use of science and medicine, which can potentially deprive minors with the protections that they are owed under US and international laws, and which may have devastating consequences. We should advocate for the creation special protocols, educate law enforcement and legal actors, ensure such procedures are carried out only as a last resort and by independent actors, emphasize child protection and always put the child’s best interest at the core.